A poet of the Abbasid period Abu al-Qasim al-Zahi (Ali b. Ishaq b. Khalaf al-Zahi) 313-352 AH/925-963 CE : his life and poetry - Sindawi, Khalid (Codices Arabici antiqui, 2010)
Khalid Sindawi introduces the reader to a prominent Shi'ite poet of the Abbasid period who has been largely ignored by modern scholarship. 'Ali b. Ishaq al-Zahi (925-963 CE) is considered second only to al-Mutanabbi among the poets of this period. The first part of the book presents the historical, political and intellectual background of the poet's lifetime, framing the biographical section of this book with the poet's birth in Baghdad, his later years in Aleppo and his death. The study discusses his names, his occupation, his relations with prominent personalities of his age, such as Sayf al-Dawla and the vizier al-Hasan b. al-Muhallabi, and his conversion to Shi'ite. It then provides an account of the various themes in his poetry and gives an analysis of the technical aspects of al-Zahi's poetry, its language, style and rhetorical devices. It also discusses the transmitters of his poetry, opinions of ancient and modern critics, and cases of plagiarism of his verse. The book's second part consists of a scholarly analysis of the poems which have survived in various traditional collections. There are fifty-four poems with three-hundred-and-seven verses in total. The final section presents the verses as they have been extracted from the various sources and closes with a detailed commentary of all the poems.